Quality of Life of Patients on Peritoneal Dialysis and Contributing Factors: A Cross-Sectional Study (Journal of Renal and Hepatic Disorders, 2023)
In recent years, interest in Health-Related Quality of Life (HRQoL) as a major indicator of clinical efficacy and treatment outcome in patients of End-Stage Renal Disease (ESRD) has grown significantly. This study aimed to determine the contributing factors affecting the quality of life (QoL) of ESRD patients undergoing peritoneal dialysis (PD). A cross-sectional study was conducted on PD patients presented at PD centres of Al-Zahra and Noor hospitals in Isfahan, Iran, from May to August 2019. A total of 173 patients having peritoneal dialysis for more than 3 months filled the validated 36-item short-form health survey questionnaire (SF-36). Baseline demographic details and dialysis-related factors were collected from patients’ medical records. The overall QoL score of patients was 50.28 ± 20.87. Male patients had a higher QoL score than female patients (58.18 in males, compared to 48.18 in females; P = 0.04). A significant association between frequency of dialysis and quality of life was observed, where three sessions of dialysis per day yielded the highest quality of life (QoL score = 59.62; P = 0.047). A significant positive correlation was discovered between QoL score and residual renal function (P = 0.013). In addition, a higher QoL score was observed in self-employed patients (60.95), compared to housewives (46.49) (P = 0.001). QoL assessment should be included as an integral part of patient follow-up to evaluate treatment outcomes and implement possible interventions to improve patient’s quality of life.
Keywords: chronic kidney disease; end-stage renal disease; peritoneal dialysis; quality of life; SF-36 questionnaire